Oxygen vacancy-induced topological nanodomains in ultrathin ferroelectric films - Wei Peng (Nature Portfolio, 2021)
Abstract Oxygen vacancy in oxide ferroelectrics can be strongly coupled to the polar order via local strain and electric fields, thus holding the capability of producing and stabilizing exotic polarization patterns. However, despite intense theoretical studies, an explicit microscopic picture to correlate the polarization pattern and the distribution of oxygen vacancies remains absent in experiments. Here we show that in a high-quality, uniaxial ferroelectric system, i.e., compressively strained BaTiO3 ultrathin films (below 10 nm), nanoscale polarization structures can be created by intentionally introducing oxygen vacancies in the film while maintaining structure integrity (namely no extended lattice defects). Using scanning transmission electron microscopy, we reveal that the nanodomain is composed of swirling electric dipoles in the vicinity of clustered oxygen vacancies. This finding opens a new path toward the creation and understanding of the long-sought topological polar objects such as vortices and skyrmions.